IMPROVING THE PROFESSIONALISM OF HIGH SCHOOL TEACHERS THROUGH ASSISTANCE IN THE DEVELOPMENT OF INDEPENDENT CURRICULUM ASSESSMENT INSTRUMENTS AT SMAN MANDE, CIANJUR REGENCY - Tjalla, Awaluddin; Ridwan, Achmad; Sarifah, Iva; Komarudin, Komarudin; Rahayu, Wardani; Riyadi, Riyadi; Yunida, Helvy; AFRIADI, BAMBANG; Salman, Ibnu; Widodo, Eko (PT. BATARI EDU CALYA, 2023)
The current era of digitalization is experiencing very rapid changes. To adjust this, very fast adaptation is needed. Starting from the development of the younger generation in this era, we are currently in the revolution of industry 4.0. The industrial revolution 4.0 is marked by rapid developments in the IT world. The key is in several words such as automation, big data analysis, robot technology, artificial intelligence (AI), to the internet of things (IoT). While many are still adapting to the industrial revolution 4.0, the discourse about the next revolution is the Industrial Revolution 5.0 where in this era it takes knowledge, skills and character of the younger generation who are able to quickly adopt and adapt to the new technology. To keep up with this era, teacher professionalism is needed in order to educate students to become a young generation who are able to move quickly to adapt to the environment. Conducting Community Service through improving the professionalism of SMAN Mande teachers through assistance in the development of the Merdeka curriculum assessment instrument is one of the strategies to support as a support system to realize that era. A teacher with high professionalism will be able to increase the capacity and capability of his students, so that they can welcome the era of the industrial revolution 4.0 and 5.0.